2011
DOI: 10.1143/jjap.50.06gm08
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Reduction of Tactile Sensor Array with Projected Cylindrical Elastomer over Sensing Element

Abstract: A tactile sensor array covered by a projected cylindrical elastomer has been designed and fabricated for crosstalk reduction among sensor elements caused by the lateral deformation of the elastomer. The analysis of elastomer deformation by the finite element method showed that the optimal thickness of the flat elastomer between cylinders and the substrate is 50–100 µm, because the sensor structure has not only a low crosstalk but also a high robustness. A tactile sensor array having the flat elastomer of 70 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In this study, we have proposed a tactile sensor with microcantilevers embedded in the elastomer (polydimethylsiloxane; PDMS) for dexterous robots and fabricated by MEMS technologies. It is demonstrated that the fabricated tactile sensors can detect normal and shear forces simultaneously [30][31][32][33][34]. In the following section, the tactile sensors with sensitive cantilevers are described, and a fabricated tactile sensor array was applied for slippage detection when the object is held in the robot's hands and is slipped.…”
Section: Miniature Tactile Sensor Wiht Piezoresistive Micro-cantilevermentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have proposed a tactile sensor with microcantilevers embedded in the elastomer (polydimethylsiloxane; PDMS) for dexterous robots and fabricated by MEMS technologies. It is demonstrated that the fabricated tactile sensors can detect normal and shear forces simultaneously [30][31][32][33][34]. In the following section, the tactile sensors with sensitive cantilevers are described, and a fabricated tactile sensor array was applied for slippage detection when the object is held in the robot's hands and is slipped.…”
Section: Miniature Tactile Sensor Wiht Piezoresistive Micro-cantilevermentioning
confidence: 99%
“…The analysis of elastomer deformation by the finite element method showed that the optimal thickness of the flat elastomer on the substrate except for the cylinders is 50-100 μm, because the sensor structure has not only a low crosstalk but also considerable robustness [34]. A tactile sensor array having the flat elastomer of 70 μm thickness has little crosstalk and high robustness.…”
Section: Friction Measurement By Moving Tactile Sensor On Objectmentioning
confidence: 99%
“…In our previous works, we developed a multiaxial MEMS tactile sensor that can detect normal and shear forces using microcantilevers with a NiCr strain gauge film. (17)(18)(19)(20)(21)(22)(23) This sensor has been applied to tactile texture measurement, thereby enabling qualitative classification of many kinds of objects. (24)(25)(26)(27) However, more quantitative tactile characterization is required to evaluate physical properties such as the hardness, thickness, and roughness of an object.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a conceptual illustration of the MEMS sensor, a microscopic image of the microcantilevers, and the cross-sectional structure of the microcantilever. (19)(20)(21)(22)(23) The microcantilevers are embedded in polydimethylsiloxane (PDMS). The microcantilever has a sloping form in order to be sensitive to both normal and shear forces.…”
Section: Introductionmentioning
confidence: 99%
“…This sensor can detect normal and shear forces simultaneously. [13][14][15][16][17][18] However, there appear some problems. One of the serious problems is the signal noise in the sensor output generated in the long wire from the sensor elements to the signal amplifier of integrated circuit (IC).…”
Section: Introductionmentioning
confidence: 99%